Conducting economic valuation surveys during extreme events - Mourato, Susana (OECD Publishing, 2021)
There is no guidance on how to deal with the effects of catastrophic events, like the COVID-19 pandemic, on stated preference survey responses, despite the possible impact such events can have on stated values and survey responses. This paper provides a concise analysis of the likely effects of extreme events on stated preference surveys, focusing on the validity and temporal stability of estimated values, and offers a set of recommendations. These recommendations can also be of use for designing other types of household and individual surveys, beyond economic valuation surveys
Keywords: Environment